Does inattentiveness matter for DSGE modelling? An empirical investigation - Jenyu Chou; Joshy Z. Easaw; Patrick Minford (Cardiff University, Cardiff Business School, 2021)
The purpose of this paper is to investigate the empirical performance of the standard New Keynesian dynamic stochastic general equilibrium (DSGE) model in its usual form with full-information rational expectations and compare it with versions assuming inattentiveness- namely sticky information and imperfect information data revision. Using a Bayesian estimation approach on US quarterly data (both real-time and survey) from 1969 to 2015, we find that the model with sticky information fits best and is the only one that can generate the delayed responses observed in the data. The imperfect information data revision model is improved fits better when survey data is used in place of real-time data, suggesting that it contains extra information.
Keywords: C11; C32; C52; E10; E12; E17; 330; Expectation formation; Inattentive expectation; New Keynesian; DSGE; Bayesian estimation